2017
DOI: 10.1099/mic.0.000502
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa gbdR gene is transcribed from a σ54-dependent promoter under the control of NtrC/CbrB, IHF and BetI

Abstract: Pseudomonasaeruginosa uses choline as a source of carbon and nitrogen, and also for the synthesis of glycine betaine, an osmoprotectant under stress conditions such as drought and salinity. The transcription factor GbdR is the specific regulator of choline metabolism and it belongs to the Arac/XylS family of transcriptional regulators. Despite the link between choline catabolism and bacterial pathogenicity, gbdR regulation has not been explored in detail. In the present work, we describe how gbdR transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…These non-coding RNAs regulate the activity of the Crc/Hfq complex by direct binding, thereby interfering with the translation repression of the corresponding mRNA targets in the process of catabolite repression in Pseudomonas and Azotobacter , corresponding to a post-transcriptional regulation mechanism. In addition, cross-talk with NtrBC regulatory systems for the assimilation of certain amino acids as a carbon or nitrogen source has been reported [ 32 , 33 , 34 , 35 ], as well as possible interactions with extracytoplasmic function (ECF) sigma factors [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…These non-coding RNAs regulate the activity of the Crc/Hfq complex by direct binding, thereby interfering with the translation repression of the corresponding mRNA targets in the process of catabolite repression in Pseudomonas and Azotobacter , corresponding to a post-transcriptional regulation mechanism. In addition, cross-talk with NtrBC regulatory systems for the assimilation of certain amino acids as a carbon or nitrogen source has been reported [ 32 , 33 , 34 , 35 ], as well as possible interactions with extracytoplasmic function (ECF) sigma factors [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa PAO1 encodes 16 known and 41 potential TRs from the AraC/XylS family (based on NCBI and pseudomonas.com databases), which makes this group one of the largest among TR families in P. aeruginosa . Most of the AraC family TRs thus far characterized in this bacterium are described as involved in the regulation of metabolism: OruR (PA0831) is an ornithine degradation activator [ 17 ], ArgR (PA0893) controls arginine biosynthesis and aerobic catabolism [ 18 ], AntR (PA2511) is an activator of anthranilate degradation [ 19 ], MmsR (PA3571) is a positive regulator of amino acid biosynthesis [ 20 ], SouR (PA4184) is essential for growth on sarcosine [ 11 ], PchR (PA4227) regulates pyochelin biosynthesis [ 21 ], GbdR (PA5380) controls choline metabolism [ 22 ], CdhR (PA5389) regulates carnitine metabolism [ 23 ], and PruR (PA0780) is a proline utilization regulator important for virulence [ 24 ]. Some of the TRs from the AraC/XylS family play different roles in P .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the σ 54 factor regulates the glyoxylate pathway, ethanolamine catabolism, ( R )-3-hydroxybutyrate, the glycine cleavage system, and pyocyanin biosynthesis via EatR, HbcR, and GcsR, respectively [ 42 , 43 , 44 , 45 ]. Other EBPs, including PhhR, FleQ, AlgB, FhpR, CbrB, NtrC, DctD, FleR, RtcR, PilR, SfnR1, AauR, and Sfa3, and their regulatory roles in metabolism, motility, and virulence have also been studied in P. aeruginosa [ 13 , 15 , 46 , 47 , 48 , 49 , 50 , 51 ]. These results indicated that the σ 54 factor forms a complex regulatory network with these EBPs, and whether these EBPs have overlapping regulatory roles needs further study.…”
Section: Introductionmentioning
confidence: 99%